Diagnostic Choices and Clinical Outcomes in Octogenarians and Nonagenarians with Iron‐Deficiency Anemia in the Netherlands. Issue 4 (21st March 2013) - Hamaker, Marije E.; Acampo, Tessa; Remijn, Jasper A.; van Tuyl, Sebastiaan A.C.; Pronk, Apollo; van der Zaag, Edwin S.; Paling, Heleen A.; Smorenburg, Carolien H.; de Rooij, Sophia E.; van Munster, Barbara C.
<x xml:space="preserve">Abstract</x> Objectives To evaluate current clinical practice for octogenarians with iron‐deficiency anemia (IDA) by assessing referral patterns, diagnostic choices, clinical consequences of omission of endoscopy, and risks and benefits of IDA‐related surgery. Design Chart review. Setting A regional hospital‐based laboratory in the Netherlands between January 2008 and December 2010. Participants All individuals aged 80 and older with newly ascertained IDA. Measurements IDA was defined as a hemoglobin level of 11.1 g/dL or less and a ferritin level of 25 μg/L or less. Results Four hundred seventy‐one participants were newly diagnosed with IDA during the study period (median age 85.4), 276 of whom (59%) did not undergo any diagnostic procedures for IDA. A cause of anemia was identified during the initial examination in 50% of the 205 investigated participants, including nine (4%) upper and 37 (18%) lower gastrointestinal malignancies. Another 24 malignancies were identified during follow‐up, of which 16 were in the gastrointestinal tract, primarily in participants for whom the initial diagnostic examination was limited or omitted. Perioperative mortality was 15% in individuals with colon cancer. Median survival for participants with colon cancer was 2.2 years, and the survival benefit of surgery over supportive care was not apparent until 1.3 years after ascertainment of IDA. Conclusion The omission of endoscopy for IDA and the omission of surgery for colon cancer occur frequently in octogenarians and seem appropriate in the presence of significant comorbidity and in cases in which there is limited life expectancy. Further research is needed to determine which baseline factors should guide decision‐making to optimize treatment outcomes and quality of life.